2009
DOI: 10.3945/ajcn.2008.26568
|View full text |Cite
|
Sign up to set email alerts
|

Folate and one-carbon metabolism nutrients from supplements and diet in relation to breast cancer risk

Abstract: Background: Few epidemiologic studies have examined very high intakes of folate and whether consumption of nutrients involved in one-carbon metabolism is associated with breast cancer risk. Objective: We prospectively examined whether the consumption of folate and nutrients involved in one-carbon metabolism (methionine, riboflavin, and vitamins B-6 and B-12) from self-reported intakes of diet (in year before baseline) and supplements (averaged over 10 y before baseline) were associated with the incidence of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
114
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(134 citation statements)
references
References 62 publications
13
114
1
5
Order By: Relevance
“…Recently, several studies reported a protective effect of folate intake on breast cancer risk Yang et al, 2013;Islam et al, 2013). However, evidence from two recent studies have indicated an inverse association (Ericson et al, 2007;Maruti et al, 2009a), and some other studies have shown that the reduced risk only exists in certain populations, such as women with high levels of alcohol intake or premenopausal Chinese women (Levi et al, 2001;Shrubsole et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…Recently, several studies reported a protective effect of folate intake on breast cancer risk Yang et al, 2013;Islam et al, 2013). However, evidence from two recent studies have indicated an inverse association (Ericson et al, 2007;Maruti et al, 2009a), and some other studies have shown that the reduced risk only exists in certain populations, such as women with high levels of alcohol intake or premenopausal Chinese women (Levi et al, 2001;Shrubsole et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…At least 30 different enzymes are involved in this complex pathway including methylenetetrahydrofolate reductase (MTHFR), methionine synthase, methionine synthase reductase, and thymidylate synthase (Kim et al, 1999;Suleeporn et al, 2010). Defects or polymorphic enzymes may alter the bioavailability of FA and influence cancer susceptibility (Maruti et al, 2009). MTHFR is responsible for the availability of methyl groups for biological methylation reactions and catalyzes the conversion of 5, 10-methylenetetrahydrofolate to 5-methyltetrahydrofolate, which is a co-substrate for homocysteine remethylation to methionine (Dhillon et al, 2009); mutations of MTHFR will alter the activity of the enzyme.…”
Section: Interactions Between Mthfr C677t -A1298c Variants and Folic mentioning
confidence: 99%
“…Choline can convert to betaine, which can donate the methyl group to homocysteine as does folate, although the donation of the methyl group by betaine is limited to the liver and the kidney. Although two meta-analyses did not find an overall association between folate intake and breast cancer risk (Lewis et al, 2006;Larsson et al, 2007), in some studies, folate intake was inversely associated with breast cancer risk in the whole population (Ericson et al, 2007), or among alcohol drinkers (Zhang et al, 1999;Rohan et al, 2000), or with certain hormone receptor types of breast cancer (Zhang et al, 2005;Larsson et al, 2008;Maruti et al, 2008). Choline and betaine may reduce the risk of breast cancer in a manner similar to that of folate.…”
mentioning
confidence: 99%